(3GdOQ GdefKhQ aj GdfgL GdefUhQs - (3eMeO Hf CMeO GdYhaj,J (B1050 (3g` s
(3ChdgG (B:s
(3hHYO jbh CVYa YHGOGddg eMeO Hf CMeO GdYhaj aj gPG GdeNJUQ Ydi PcQ bQGAGJ GdCFeI GdYTQ MSH WQjb GdTjN GdCSJGP GdUGdM CHheMeO CMeO GdeSjQj s
(3BNQgG (B:s
(3hgh GdPj aj GdCUd hJQc CHhGdWjH Yfg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B9 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B306s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdbQGAGJ hGdJLhjOs